The limitations of using risk factors to screen for blunt cerebrovascular injuries: the harder you look, the more you find. Issue 1 (December 2015) - Jacobson, Lewis; Ziemba-Davis, Mary; Herrera, Argenis
Abstract Introduction Blunt cerebrovascular injury (BCVI) is reported to occur in 1–2 % of blunt trauma patients. Clinical and radiologic risk factors for BCVI have been described to help identify patients that require screening for these injuries. However, recent studies have suggested that BCVI frequently occurs even in the absence of these risk factors. The purpose of this study was to determine the incidence of BCVI in blunt trauma patients without risk factors and whether these patients could be identified by a more liberal CTA screening protocol. Methods We conducted a retrospective cohort study of all blunt trauma patients seen between November 2010 and May 2014. In May 2012, a clinical practice guideline for CTA screening for BCVI was implemented. The records of all patients with BCVI were reviewed for the presence of risk factors for BCVI previously described in the literature. Results During the 43 month study period, 6, 602 blunt trauma patients were evaluated, 2, 374 prior to, and 4, 228 after implementation of the clinical practice guideline. Nineteen percent of all blunt trauma patients underwent CTA of the neck after protocol implementation compared to only 1.5 % prior to protocol implementation (p = 0.001). As a result, a 5-fold increase in the identification of BCVI was observed (p = 0.00003). Thirty-seven percent of patients with BCVI identified with the enhanced CT screening protocol had none of the signs, symptoms, or risk factors usually associated with these injuries. Conclusions Our findings demonstrate that reliance on clinical or radiologic risk factors alone as indications for screening for BCVI is inadequate. We recommend routine CTA screening for BCVI in all patients who have sustained a mechanism of injury sufficient to warrant either a CT of the cervical spine or a CTA of the chest.